2010
DOI: 10.1074/jbc.m109.046284
|View full text |Cite
|
Sign up to set email alerts
|

Fbxo45, a Novel Ubiquitin Ligase, Regulates Synaptic Activity

Abstract: Neurons communicate with each other through synapses. To establish the precise yet flexible connections that make up neural networks in the brain, continuous synaptic modulation is required. The ubiquitin-proteasome system of protein degradation is one of the critical mechanisms that underlie this process, playing crucial roles in the regulation of synaptic structure and function. We identified a novel ubiquitin ligase, Fbxo45, that functions at synapses. Fbxo45 is evolutionarily conserved and selectively expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…Therefore, we analyzed whether different components of the ubiquitin proteasome complex might be involved in CEversus TSEC-mediated ERa degradation. ERE-DNA pulldown assays coupled with mass spectrometry analyses revealed that FBXO45, a component of an E3 ubiquitin ligase complex (Saiga et al, 2009;Tada et al, 2010), was significantly recruited to the ERa/ERE complex in the presence of TSEC compared with vehicle (Fig. 4, C and D).…”
Section: Dual Inhibition Of Era By Tissue-selective Estrogen Complexmentioning
confidence: 99%
“…Therefore, we analyzed whether different components of the ubiquitin proteasome complex might be involved in CEversus TSEC-mediated ERa degradation. ERE-DNA pulldown assays coupled with mass spectrometry analyses revealed that FBXO45, a component of an E3 ubiquitin ligase complex (Saiga et al, 2009;Tada et al, 2010), was significantly recruited to the ERa/ERE complex in the presence of TSEC compared with vehicle (Fig. 4, C and D).…”
Section: Dual Inhibition Of Era By Tissue-selective Estrogen Complexmentioning
confidence: 99%
“…Taken together, these finding are in nice accord with data obtained in C. elegans, further supporting the notion that Highwire/RPM-1 and FSN operate in the same pathway with DLK as a major target 122,125 . Even in mammals, the Highwire/RPM-1 and FSN orthologues, Phr1 and Fbxo45, seem to function in a complex at synapses 126,127 , but this complex may have neuronal targets other than DLK 128 .…”
Section: Ubiquitination and Synapse Formation In Invertebratesmentioning
confidence: 99%
“…The peptide sequence was used to generate antisera as previously described. 10 Flow cytometry analysis. For measuring apoptosis, transfected cells were dual stained with 7-AAD (PE) and APC-Annexin V using an Alexa Fluor 488-annexin V Dead Cell apoptosis kit (Invitrogen) according to the manufacturer's protocol.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Fbxo45 has been linked to the proteasomal degradation of a few targets including p73 9 and Munc13-1. 10 Fbxo45 is one of only six F-box proteins that are conserved in metazoans and the only F-box protein known to contain a SPRY domain, 3 which was first identified as a sequence repeat in the dual-specificity kinase splA and ryanodine receptors. 11 SPRY domains are present in more than 150 human proteins that cover a wide spectrum of biological functions, including regulation of cytokine signaling and innate retroviral restriction.…”
mentioning
confidence: 99%